Chester Beatty Cpt 2039: A New Bodmer Fragment among the Chester Beatty Papyri - Sharp, Daniel B. (Journal of Coptic studies, 2025)
This note provides a description and transcription of a fragment of the Bodmer manuscript P. Bodmer 18 that was discovered among the Chester Beatty Papyri. Additionally, in an attempt to assist researchers interested in understanding the connections between the Bodmer and Beatty collections, it provides an updated list of all manuscripts that overlap in the two collections.